Assessment of antibiotic prescribing patterns in practising doctors: Clinical study - Srikanth Reddy Karra (Bioinformation, 2026)
Inappropriate and empirical antibiotic prescription by practising physicians remains a major contributor to the growing global burden of antimicrobial resistance (AMR). Therefore, it is of interest to assess the antibiotic prescribing patterns among practising doctors and identify common trends in drug selection, indications and adherence to prescribing guidelines. A cross-sectional clinical evaluation of prescriptions issued by practising physicians was conducted and analysed using descriptive statistical methods. The results showed that broad-spectrum antibiotics and empirical therapy were frequently prescribed, often for conditions where antibiotics were not clinically indicated. Thus, data shows the need for stronger antimicrobial stewardship strategies and continuing medical education to optimize rational antibiotic prescription practices.